2013
DOI: 10.1002/poc.3194
|View full text |Cite
|
Sign up to set email alerts
|

Formation of diazohydroxides ArN2OH in aqueous acid solution: polarographic determination of the equilibrium constant KR for the reaction of 4‐substituted arenediazonium ions with H2O

Abstract: In aqueous acid (pH <4) solutions, in the dark, and in the absence of reductants, arenediazonium ions, ArN 2 + decompose spontaneously through the rate-limiting formation of the extremely unstable aryl cation that reacts with any nucleophile present in its solvation shell (D N + A N mechanism). However, in weak acidic and alkaline solutions, + to determine, for the first time, the equilibrium constants K R of formation of 4-substituted X-ArN 2 OH (X¼H, Me, MeO, Br, and NO 2 ), which can decompose in several wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…On the basis of the work of Bravo-Díaz and co-workers, we will briefly examine the different species that are present in a diazonium solution depending on the acidity of the medium. In ACN, the diazonium cation is present, but in an aqueous medium, the diazonium cation, diazohydroxide, and diazoate species can be present depending on the pH. In aqueous acidic (pH <4) solutions, in the dark and in the absence of reductants, arenediazonium ions, ArN 2 + , decompose spontaneously through the rate-limiting formation of the extremely unstable aryl cation.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the work of Bravo-Díaz and co-workers, we will briefly examine the different species that are present in a diazonium solution depending on the acidity of the medium. In ACN, the diazonium cation is present, but in an aqueous medium, the diazonium cation, diazohydroxide, and diazoate species can be present depending on the pH. In aqueous acidic (pH <4) solutions, in the dark and in the absence of reductants, arenediazonium ions, ArN 2 + , decompose spontaneously through the rate-limiting formation of the extremely unstable aryl cation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context heterolytic dediazoniation has been reported to occur with ortho-, meta-and para-methylbenzenediazonium (2MBD, 3MBD, 4MBD) and para-nitrobenzenediazonium (4NBD) ions in an aqueous medium [10,22], while other authors interpreted their results as showing evidence of heterolytic and homolytic processes during the thermal and photochemical dediazoniation of several arenediazonium ions in trifluoroethanol and ethanol [19][20][21]. However, in our latest article, we demonstrated that, at moderate pH, water can act as nucleophile giving rise to a diazohydroxide, which eventually can decompose to give radical products [23].…”
Section: Introductionmentioning
confidence: 76%
“…Diazonium ions have proved to be very sensitive to their environment, [1,14,22,23] and thus proper understanding of their behaviour in the micellar systems is of great importance [14-16, 24,25]. Hydrophobicity of arenediazonium ion and charge of the micelle are believed to be the most important factors affecting the localization of ions in the micellar system.…”
Section: Resultsmentioning
confidence: 99%
“…This extinction coefficient is lower than that of the anti -diazotate and corresponds more closely to that of the diazohydroxide 11 whose formation has been recently inferred by electrochemical means. 19 Aryl diazonium compounds with highly electron-withdrawing substituents on the benzene ring, such as the nitro and cyano groups, demonstrate a faster rate of aqueous hydroxide combination to produce a more acidic diazohydroxide. 16,20 This product is indeed almost absent under the conditions of purely aqueous reaction because of rapid proton loss 21 but is expected to be stabilized with respect to the anionic diazotate in the less polar 50% ACN solvent.…”
Section: Resultsmentioning
confidence: 99%